SIBIKU SIGN LANGUAGE APPLICATION INTRODUCION FOR JUNIOR AND SENIOR HIGH SCHOOL STUDENTS AT SLB NEGERI 2 DENPASAR - Dewanti, Paula; Indriyani, Indriyani (Community Development Journal : Jurnal Pengabdian Masyarakat, 2023)
Hearing impaired is the condition of a person who experiences a deficiency or loss of the sense of hearing so that they are unable to perceive stimuli in the form of sounds, voices, or the like, which results in normal communication skills being unable to be carried out properly by people with hearing loss They need sign language for communication between them and normal people. Due to hearing difficulties, exclusive learning is needed using learning media in the form of a sign language dictionary to recognize vocabulary in sign language. The SIBIKU application was created to make it easier for hearing-impaired people to learn sign language vocabulary with features from the SIBIKU application, which uses moving images to make it easy to model sign language movements. There is also a Morse vibration feature, which converts numbers and letters into Morse in the form of vibrations generated by the user’s smartphone. And for practice materials, this application has a sign word guessing feature as an evaluation material for learning sign language vocabulary. With dynamic data, it is hoped that the SIBIKU application can help solve problems faced by teachers and children with hearing loss at SLB Negeri 2 Denpasar in learning sign language vocabulary.